2001
DOI: 10.1016/s0886-3350(00)00699-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved prediction of intraocular lens power using partial coherence interferometry

Abstract: Partial coherence interferometry biometry applied to several widely used IOL power formulas yielded significantly better IOL power prediction and therefore refractive outcome in cataract surgery than US biometry. Further improvement can be achieved by applying PCI to a modified SRK/T formula that predicts the postoperative ACD using PCI biometry data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
96
2
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(110 citation statements)
references
References 32 publications
5
96
2
4
Order By: Relevance
“…Further, the precision achieved with partial coherence laser interferometry was shown to be 10 times better than that of ultrasound in earlier studies. 16,17 The data from our study show that there is a tendency for hyperopic shift in eyes that undergo partial coherence laser interferometry. This is probably because the axial lengths are measured approximately 100 m longer than with applanation ultrasound.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Further, the precision achieved with partial coherence laser interferometry was shown to be 10 times better than that of ultrasound in earlier studies. 16,17 The data from our study show that there is a tendency for hyperopic shift in eyes that undergo partial coherence laser interferometry. This is probably because the axial lengths are measured approximately 100 m longer than with applanation ultrasound.…”
Section: Discussionmentioning
confidence: 67%
“…Other studies have shown an improvement in predictive value up to 27%. 16,17 It is possible to achieve better predictive value with PCLI by altering the A-constant. However we did not alter the A-constant in this study.…”
Section: Discussionmentioning
confidence: 99%
“…1 The Royal College of Ophthalmologists (RCOphth) 2004 cataract surgery guidelines state that both optical (partial coherence interferometry (PCI)) and acoustic (ultrasound) methods of axial length measurement can be routinely used, 2 although it has been shown that PCI reduces the prediction error of postoperative refractive outcome. [3][4][5] The RCOphth 2004 guidelines state that each ophthalmology department, if not each surgeon, should personalise the A constant on the basis of continuous audit of the comparison of the predicted and actual spherical equivalent of the postoperative subjective refraction.…”
Section: Introductionmentioning
confidence: 99%
“…2,6,7 Setting a benchmark standard would allow all National Health Service (NHS) cataract services to know whether they are achieving a satisfactory standard. It has previously been suggested, 1,8 based upon studies, [3][4][5][6] that a benchmark of 85-90% of patient undergoing routine cataract surgery should achieve a final spherical equivalent refraction within 1 D of the predicted value.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The benefits of customising A constants are easy to apply to NHS departments by routinely performing biometry calculations using appropriate software. Cataract surgery is one of the most commonly performed operations in the UK, and it is clear from this study that very few eye departments are appropriately auditing their biometry service and acting on the results.…”
Section: Discussionmentioning
confidence: 99%